2020
DOI: 10.4132/jptm.2019.10.08
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune response and immunotherapy in gastric cancer

Abstract: Recent studies have reported the promising results of immunotherapy in many solid tumors [1]. Unlike traditional cancer therapy, which targets the tumor directly, immunotherapy offers a different approach and is an alternative treatment option for patients with cancer. Because immunotherapy generally engages immune reactions to recognize and eliminate tumor cells, demand for understanding the tumor immune response has increased. Resulting from increased study, novel biomarkers associated with the tumor immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 111 publications
3
59
0
Order By: Relevance
“…Taken together, these results support the hypothesis that epigenetic silencing of MLH1 functions as a repressive transcriptional signal. The commonly accepted association of MLH1 and MMR-deficient gastric cancers is also confirmed by these data [23][24][25]. We further evaluated how mutational activity is modulated in our MMRD and MMRP groups ( Figure 6C,E,F).…”
Section: Image Classification Recapitulates Unique Molecular Driverssupporting
confidence: 76%
“…Taken together, these results support the hypothesis that epigenetic silencing of MLH1 functions as a repressive transcriptional signal. The commonly accepted association of MLH1 and MMR-deficient gastric cancers is also confirmed by these data [23][24][25]. We further evaluated how mutational activity is modulated in our MMRD and MMRP groups ( Figure 6C,E,F).…”
Section: Image Classification Recapitulates Unique Molecular Driverssupporting
confidence: 76%
“…STAD is Helicobacter pylori-induced chronic gastritis, and frequently characterized by the immune cell infiltration, containing granulocytes, macrophages, and T lymphocytes [8,9]. Tumor-associated lymphocytes (TALs), primarily T cells, are the major type of infiltrating immune cells in cancer tissues, and produce soluble cytokines that regulate the proliferation and migration of cancer cells, promote angiogenesis, and participate in activation of host defense mechanism [10][11][12]. In STAD, tumor-associated macrophages (TAMs) infiltration into tumor tissue was correlates significantly with tumor vascularity, the depth of tumor invasion, lymph node status and clinical stages [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, several clinical trials are currently ongoing with various strategies. 30 31 The phase III ATTRACTION-04 (NCT02746796) trial is evaluating nivolumab plus standard chemotherapy (oxaliplatin plus either S-1 or capecitabine) versus chemotherapy alone in Asian patients. 16 The phase II component (part 1) of this study showed chemotherapy plus nivolumab led to an ORR of 65.8% and median PFS of 9.5 months, while the subsequent phase III trial (part 2) is evaluating the survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 14 In situ hybridisation detection of EBV-encoded small RNA in tumour cells is generally recommended to identify EBV-associated GC (EBVaGC). 30 The incidence of EBVaGC varies from 1% to 30% in different regions with an average of 10% worldwide. 45 Nevertheless, this subgroup is associated with better prognosis, thus less frequently found in advanced or metastatic setting.…”
Section: Introductionmentioning
confidence: 99%